A molecular genetic lab to generate inclusive and exclusive forensic evidence: Two suspects, a victim, and a bloodstained T‐shirt. Issue 3 (20th December 2013) - Smit, Julie; Heath, Daniel D.; Walter, Ryan P.
Abstract Molecular genetic laboratory exercises can be ineffective due the student's lack of connection to the complex and sequential protocols. In this inquiry‐based molecular genetic laboratory exercise, we harness students' fascination with human forensics and provide a real‐life scenario using biomolecular techniques to identify "whose blood is on the t‐shirt." We use fish blood to create realistic blood stains on clothing and challenge the students to use DNA analyses to clear or implicate suspects. Safety concerns are minimized through the use of fish blood, while maximizing both realism and the likelihood of student success due to fishes' nucleated red blood cells. The goal in designing this laboratory exercise was to create a feasible protocol for large (over 300 students) second year university courses. During two 3 hour laboratory sessions, students learn and apply clean/sterile technique, DNA extraction, polymerase chain reaction, restriction fragment length polymorphisms, and agarose gel electrophoresis. The students also learn to interpret the resulting gel bands in terms of inclusive or exclusive evidence. Students have consistently ranked this lab as their favorite of five taken as part of a second year Genetics course. © 2013 by The International Union of Biochemistry and Molecular Biology, 42(3):XXXXX–XXXXX, 2014.